The Implementation of Transformational Leadership to Improve Teacher Performance - Fususul Khair (International Research-Based Education Journal, 2021)
This research aims to describes how tranformasional leadership and its implementation in improving teacher performance. The research uses literature review research method by collecting data from various sources of literature both print and online internet that can be used as reference. The results for the implementation process of the principal's transformational leadership are idealization of influence that is to be a good example and foster pride for the school community, creating a conducive learning process and school organizational climate and having a positive perception of managing school.